Investigation into attitudes towards older people with dementia in acute hospital using the Approaches to Dementia Questionnaire. (November 2020) - de Vries, Kay; Drury-Ruddlesden, Jenny; McGill, George
Background: Health care professionals have poor recognition of cognitive impairment among older patients and often have difficulties in providing care for people with dementia in acute hospitals. There are also reported high levels of stigma and negative staff attitudes towards people with dementia. Methodology: A one-time survey of staff working on acute medical and orthopaedic wards of five District Health Boards in New Zealand using the 'Approaches to Dementia Questionnaire'; a 19-item Questionnaire that aims to capture two attitudinal domains (Hope and Person-Centredness), towards people with dementia. A total of 563 questionnaires were distributed. Data were analysed using R. Results: Three hundred and four (53.99%) respondents completed the survey. Ninety-four of the respondents (31.1%) were aged 51 years or older, and nearly all (88.4%) were women. One hundred and sixty-four of the respondents (53.9%) were registered nurses, 10 were student nurses (3.3%), 24 (7.9%) were healthcare assistants, 70 (23.0%) were allied health professionals, 27 (8.9%) were doctors and 9 (3%) were pharmacists. The mean total score of 72.7 reflected positive attitudes overall on the part of the respondents. Allied health professionals, student nurses and pharmacists had high scores on both scales whilst healthcare assistants scored lowest on both scales. Conclusion: Overall, the Approaches to Dementia Questionnaire is a useful measure, but it can be difficult to differentiate between genuine attitudinal differences and confounding influences such as level of knowledge and education amongst such a diverse group of participants. Differences between staff may be considered as a reflection of the high level of direct care that is expected of some staff and not of others. Further, the Approaches to Dementia Questionnaire may not be the most appropriate measure to accurately understand attitudes to dementia care in acute environments; and that it more usefully reveals knowledge about dementia rather than attitudes related to real-time practice.